Mengatasi Defisit Dana Jaminan Sosial Kesehatan Melalui Perbaikan Tata Kelola - Annisa, Raisa; Winda, Syahdu; Dwisaputro, Erlangga; Isnaini, Kartika Nur (Komisi Pemberantasan Korupsi, 2020)
Celebrating its fifth-year of implementation, the National Health Insurance System (NHIS) have been facing several problems including the chronic deficit on Healthcare and Social Security Fund (HSSF) up to 11,69 Trillion Rupiah. Using a descriptive qualitative and quantitative method, The Corruption Eradication Commission conducted a research to examine the cause of deficit by looking at the governance and corruption prevention mechanism in this policy. The result of this study highlights and suggests significant improvement on strategic purchasing policies, operational side, and contribution collection, so that the NHIS program can run more effectively, efficiently, and also able to close the loopholes